Infographic: Meniscal transplantation is beneficial at one year. (January 2018) - Smith, N. A.; Parsons, N.; Wright, D.; Hutchinson, C.; Metcalfe, A.; Thompson, P.; Costa, M. L.; Spalding, T.
Abstract :